Estimation of postmortem interval using the blowfly Phaenicia (Lucilia) sericata (Diptera: Calliphoridae) in Kaduna, Northern Nigeria - Ahmed, Ado-Baba; Joseph, Samson G. (International Journal of Research in Medical Sciences, 2017)
Background: The period of insect activity (PIA) was experimentally estimated for a carcass of Cavia porcellus (guinea pig) using the blowfly Phaenicia sericata in Kaduna, northern Nigeria. Methods: Cavia porcellus (guinea pig) was killed and the carcass placed inside in a wire cage measuring 81x53x45 cm to prevent larger animals and birds from scavenging and allowed to decompose under ambient conditions and an average of 12hour light and darkness. Results: Six second-instar larvae of blowflies were collected from the decomposing carcass from which four adult flies emerged and identified (two each of P. sericata and P. infernalis). Using P. sericata, the period of insect activity (PIA) was estimated as the difference between the total development time of the species and the time it required to become adult in the laboratory. The estimated minimum post mortem interval was 13.8 days with the probable day of oviposition between 9th and 10th January, 2016, coinciding with the actual period the animal was killed Conclusions: Estimated time between death and discovery of corpse (PMI) based on the period of insect activity (PIA) may be a better alternative in some situations because it eliminate taking multiple temperature measurements at the crime scene, at the carcass as well in the maggot masses on the cadaver.